Ethnics in Expressing Opinions on Social Media: The Role of Regulation, Influence of Public Opinio, Legal Awareness, Online Security, and Social Responsbility Convolutional Neural Network Method - Muhammad Caesar Akbar; Alamda Zeki Amala (Sean Institute, 2025)
Social media has become a major platform for public opinion. However, this freedom is often not accompanied by adequate ethical responsibility. This study highlights the case of